Robust Digital Watermarking Techniques for protecting copyright Applied to Digital Data: A Survey - LAKSHMAN JI, Dr. M.SIVAK KUMAR, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The colossal prominence of the World Wide Web in the mid 1990's shown the business capability of offering media assets through the computerized networks. Since business intrigues look to utilize the advanced organizations to offer computerized media revenue driven, they have a solid interest in ensuring their proprietorship rights. Since the danger of utilizing media data, advanced fabrications, and unapproved sharing (robbery) of computerized content has expanded among content makers, merchants and clients. Today mixed media data theft alone has exposed all the enterprises to multi-billion income misfortunes. Customary advanced substance security methods, for example, encryption and scrambling, alone can't give satisfactory insurance of copyrighted substance, in light of the fact that these advances can't ensure computerized content whenever they are decoded. One approach to debilitate illicit duplication is to embed data known as watermark, into possibly weak information so that it is difficult to isolate the watermark from the information. Computerized watermarking is the way toward embedding’s an advanced sign or example inside a computerized picture, which gives proof of realness. This paper presents a study on different data concealing strategies and depicts characterization of advanced Watermarking procedures.